PENGARUH PEMBERIAN ABU JANJANG KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) PADA MEDIA GAMBUT - Rika Fitry Ramanda; Beny Setiawan; Andrix Wijaya (Journal of Agro Plantation (JAP), 2022)
Oil palm (Elaeis guinensis jacq) is a crop that is a top priority in plantations in Indonesia. Peat soil as a nursery medium faces many obstacles such as physical and chemical properties that do not support plant growth. Oil palm janjang ash (AJKKS) is an ameliorant that can increase the uptake of macronutrients P, K, Ca and Mg so as to improve the physical and chemical properties of peat soil. This study aims to determine the effect of oil palm empty fruit bunch ash on the growth of oil palm seedlings on peat media. The research will be conducted at the Ketapang State Polytechnic, from January to March 2022. This study was conducted using a non-factorial completely randomized design (RAL) consisting of 5 treatments and 6 replications. Treatment D0 (AJKKS 0 g/polybag), D1 (AJKKS 150 g/polybag), D2 (AJKKS 250 g/polybag) D3 (AJKKS 350 g/polybag) D4 (AJKKS 450 g/polybag). Parameters observed were growth percentage (%), seedling height (cm), number of leaves (strand), stem diameter (mm), root length (cm), peat soil pH. The provision of AJKKS 450 g/polybag significantly affected the growth of oil palm seedlings on the growth of seedling height, number of leaves, stem diameter, number of leaves, root volume, plant dry weight, and soil pH.